Jews, Gentiles, and ethnic reconciliation : Paul's Jewish identity and Ephesians - Yee, Tet-Lim N. (Cambridge University Press, 2005)
Much recent scholarship has focused on Paul's insistence on Gentile membership of the people of God equally with Jews. This book contributes to the continuing reassessment of Christian and Jewish self-understanding during the latter decades of the first century and reveals how a distinctively Jewish world view underlies Ephesians 2.
Keywords: Bible. -- Ephesians, II -- Criticism, interpretation, etc.; Bible -- New Testament. -- Éphésiens. -- II -- Critique, interprétation, etc.; Paulus, -- Apostel, -- ca. 1. Jh. -- Epheserbrief 2.; Paulus <Apostel>; Epheserbrief 2.; Jews in the New Testament.; Gentiles in the New Testament.; Juifs dans le Nouveau Testament.; Gentils dans le Nouveau Testament.; RELIGION -- Biblical Studies -- New Testament.; RELIGION -- Biblical Studies -- Paul's Letters.; Gentiles in the New Testament; Jews in the New Testament; Heidenchristentum; Judenchristentum; Christentum; Ethnische Identität; Heidentum; Juden; Judentum; Religiöse Identität; Efeziërs (bijbelboek); Joden.; Heidenen.; Electronic books.; Criticism, interpretation, etc.